2022
DOI: 10.1088/1742-6596/2157/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of LabXChange virtual lab and PhyPhox real lab on pendulum student practicum during pandemic

Abstract: Virtual Laboratory (virtual lab) is a series of virtual experiment laboratories that have been designed and programmed to be used by students for practicum, especially during the Covid-19 pandemic. The virtual lab is helpful for student to build content knowledge which usually they do in real practicum activities. The virtual lab is arranged systematically. Therefore, the result should be close to the real value. Here we report our study on pendulum whether the virtual lab experiment yield the same result as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…The development of technology leads to innovation in interactive learning through virtual laboratory (virtual lab). Virtual lab is a series of virtual experiment laboratories that have been designed and programmed ICMScE [1]. Using a virtual lab has many advantages, including: (a) Perform time-consuming experiments in less time; (b) perform dangerous experiments in a safe environment; (c) reproduce events that are difficult to observe in physical laboratories; and (d) lower cost instead of expensive laboratories [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The development of technology leads to innovation in interactive learning through virtual laboratory (virtual lab). Virtual lab is a series of virtual experiment laboratories that have been designed and programmed ICMScE [1]. Using a virtual lab has many advantages, including: (a) Perform time-consuming experiments in less time; (b) perform dangerous experiments in a safe environment; (c) reproduce events that are difficult to observe in physical laboratories; and (d) lower cost instead of expensive laboratories [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Pusch, Ubben, Laumann, Heinicke ve Heusler (2021) ise güneş panellerinden Ardunio ile alınan verileri Bluetooth ile Phyphox uygulamasına göndererek bu güneş panelinin farklı ışık şiddetlerindeki gücünün ölçülmesi için gerekli deney basamaklarını açıklamaktadırlar. Ayrıca; Nanto, Agustina, Ramadhanti, Putra & Mulhayatiah (2022) basit sarkaç konusunda yapılan sanal laboratuvar deneylerinden elde edilen verileri, Phyphox uygulaması kullanılarak gerçekleştirilen gerçek deneylerden elde edilen veriler ile karşılaştırmışlardır. Araştırmacılar iki uygulamada alınan veriler arasında büyük bir farklılık bulunmadığını belirtmişlerdir.…”
Section: Introductionunclassified
“…Various problems arise in the laboratory activity model, one of which is the concern between real and virtual laboratories (Suryanti et al 2019). The dilemma faced by educators is when they want laboratory activities but they are not available, but when they want to do virtual laboratory activities, there is no syntactic harmony between real and virtual laboratory activities, Previous study (Nanto et al 2022) revealed in his research that sometimes laboratory activities are similar. For actual laboratory activities.…”
Section: Introductionmentioning
confidence: 99%